2016
DOI: 10.5964/ejop.v12i3.1115
|View full text |Cite
|
Sign up to set email alerts
|

Birds of a feather laugh together: An investigation of humour style similarity in married couples

Abstract: The present research investigated the degree of similarity in humour styles between spouses as assessed with the Humour Styles Questionnaire (HSQ). Furthermore, self-esteem was investigated as a potential moderator of partner humour style similarity. A sample of 116 heterosexual, married couples independently completed questionnaires assessing self-reported humour styles across the 32 item HSQ, as well as global self-esteem. Results indicated that there is significant positive association between the humour st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…One of the main predictors of whether a person likes another person is similarity ( Byrne & Nelson, 1965 ). The so-called similarity hypothesis has received a lot of support with regard to personality traits such as optimism in romantic relationships ( Böhm, Schütz, Rentzsch, Körner, & Funke, 2010 ), personality and physical attractiveness in roommate relationships ( Carli, Ganley, & Pierce-Otay, 1991 ), humor style in married couples ( Hahn & Campbell, 2016 ), gender-role self-concept and selection of dating partners ( Morell, Twillman, & Sullaway, 1989 ), socially undesirable traits such as Machiavellianism ( Ináncsi, Láng, & Bereczkei, 2016 ), and same-sex friendships regardless of duration or closeness ( Morry, 2005 ). The meta-analytic effect of interpersonal attraction and perceived similarity was estimated to be r = .39 ( Montoya, Horton, & Kirchner, 2008 ).…”
Section: Perceivers' Traits In Relation To Targets' Traitsmentioning
confidence: 99%
“…One of the main predictors of whether a person likes another person is similarity ( Byrne & Nelson, 1965 ). The so-called similarity hypothesis has received a lot of support with regard to personality traits such as optimism in romantic relationships ( Böhm, Schütz, Rentzsch, Körner, & Funke, 2010 ), personality and physical attractiveness in roommate relationships ( Carli, Ganley, & Pierce-Otay, 1991 ), humor style in married couples ( Hahn & Campbell, 2016 ), gender-role self-concept and selection of dating partners ( Morell, Twillman, & Sullaway, 1989 ), socially undesirable traits such as Machiavellianism ( Ináncsi, Láng, & Bereczkei, 2016 ), and same-sex friendships regardless of duration or closeness ( Morry, 2005 ). The meta-analytic effect of interpersonal attraction and perceived similarity was estimated to be r = .39 ( Montoya, Horton, & Kirchner, 2008 ).…”
Section: Perceivers' Traits In Relation To Targets' Traitsmentioning
confidence: 99%
“…In another study, which examined the relationship between humor types and the quality of the relationships among married and divorced individuals [54], it was found that the satisfaction obtained from marriage was high in individuals with similar humor types and that using the participatory and self-progressive humor was low among the divorced couples. Hahn and Campbell [55] found that there were significant similarities between humor types of individuals who had happy marriages. In the same study, it was found that the similarity between the humor types of couples who had high ego respect was higher [55].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hahn and Campbell [55] found that there were significant similarities between humor types of individuals who had happy marriages. In the same study, it was found that the similarity between the humor types of couples who had high ego respect was higher [55].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other novel aspects of humor styles examined in the current set of studies include: (7) the degree of similarity in humor styles between spouses ( Hahn & Campbell, 2016 , this issue), (8) childrens’ understanding of self-evaluative and self-defeating humor styles ( James & Fox, 2016 , this issue), and (9) adaptations of the Humor Styles Questionnaire for use with German speaking populations ( Ruch & Heintz, 2016 , this issue).…”
Section: Articles In the Current Special Issuementioning
confidence: 99%